Brain and liver fatty acid composition changes upon consumption of Lactobacillus rhamnosus LA68. (February 2015) - Ivanovic, Nevena; Minic, Rajna; Djuricic, Ivana; Dimitrijevic, Ljiljana; Sobajic, Sladjana; Zivkovic, Irena; Djordjevic, Brizita
Abstract Recent reports suggest that the metabolic activity of the enteric microbiota may influence the fatty acid composition of the host tissue. There are many studies dealing with the influence of lactobacilli on various pathological conditions, and some of the effects are strain-specific. This study was designed to test the effects of a particular Lactobacillus strain, Lactobacillus rhamnosus LA68 on fatty acid composition of the liver and the brain of C57BL/6 mice in the absence of an underlying pathological condition. Female mice were supplemented with live L. rhamnosus LA68 bacteria for the duration of 1 month. Serum biochemistry was analyzed and liver and brain fatty acid composition was assessed by gas-liquid chromatography. Significant changes in liver and brain fatty acid composition were detected. In the liver tissue we detected an increase in palmitoleic acid (p = 0.038), while in the brain compartment we found an increase in palmitic (p = 0.042), stearic (p = 0.017), arachidonic acid (p = 0.009) and docosahexaenoic acid (p = 0.004) for control versus experimental group. These results show discrete changes caused by LA68 strain consumption. Even short duration of administration of LA68 influences the fatty acid composition of the host which adds to the existing knowledge about Lactobacillus host interaction, and adds to the growing knowledge of metabolic intervention possibilities.